Proceedings of the Cranfield Multi-Strand Conference: Creating Wealth Through Research and Innovation (CMC 2008): 6-7 May 2008 - (:unkn) unknown (Cranfield University Press, 2008)
This new Multi-Strand Conference explored how wealth is created through research and innovation. It brought together researchers and practitioners from across the spectrum to discuss advances in applied sciences, engineering and technology, including associated management practices. There was a focus on application, especially in the environment sector, manufacturing, aerospace, health and defence sectors. A particular aim was to provide a welcoming and supportive forum for early-stage researchers to present and discuss their work with more established figures in their various fields.
Organised by: Cranfield University